Critical Analysis of the Implementation of the Restorative Justice System in the Indonesian Legal System - Runtunuwu, Yoan Barbara; Mesra, Romi (Jurnal Mahkamah Hukum, 2024)
This study aims to critically analyze the implementation of restorative justice practices in Indonesia, highlighting its positive aspects, challenges, and recommendations for improvement. Research method of this article is a comprehensive review of relevant literature, including theoretical frameworks, empirical studies, and policy documents, was conducted to examine the adoption of restorative justice in the Indonesian context. The analysis focused on evaluating the cultural alignment, victim empowerment, community involvement, legal and institutional frameworks, capacity and resource constraints, and stakeholder perspectives. The findings reveal that while restorative justice aligns with traditional Indonesian values and offers a victim-centered approach and community involvement, its implementation faces significant challenges. These include the lack of a comprehensive legal framework, limited application to minor offenses, victim reluctance due to power imbalances, and capacity and resource constraints across diverse regions. To address these challenges, the study recommends developing a robust legal framework, cautiously expanding the application to certain serious offenses with robust safeguards, strengthening victim support services, investing in capacity-building initiatives, and promoting public awareness and education. Overall, the successful implementation of restorative justice in Indonesia requires overcoming legal and institutional gaps, building capacity and resources, and fostering a culture of victim empowerment, community involvement, and offender accountability. By addressing these challenges, Indonesia can pave the way for a more holistic, inclusive, and effective justice system that promotes healing, reconciliation, and social harmony.